Summer Show 2000. (London, : Marlborough Fine Art Ltd., 2000)
Abakanowicz, Magdalena ; Arikha, Avigdor ; Auerbach, Frank ; Bramham, Christopher ; Campbell, Steven ; Chen Yifei ; Conroy, Stephen ; Davies, John ; Hambling, Maggi ; Jacklin, Bill ; Kiff, Ken ; Kitaj, R.B. ; Brun, Christopher Le ; Oulton, Thérèse ; Pasmore, Victor ; Paul, Celia ; Raphael, Sarah ; Rego, Paula ; Whitely, Brett ; Williams, Fred ; Willing, Victor
biografie
Summer Show 2000, Marlborough Fine Art Ltd., London, 26 July - 22 September 2000
boek